Security Governance Strategies: Comparing Rebel Groups in Lebanon and Syria - Samir Ibrahim, Nourhan (AUC Knowledge Fountain, 2023)
The prevalence of civil wars especially after the end of the Cold War led to the rise of rebels who control parts of national states in the absence or weakness of the central government. Therefore, scholars who are interested in studying civil wars started to give more attention to how these rebels function after controlling a territory. It is substantial to study rebels who govern since they influence the post conflict peace-building. This study aimed at exploring the different factors that contribute to the sustainability of rebel governance during civil wars, and how this sustainability might lead to inclusion in the post-war political life. In order to examine these factors, the paper had to start by discussing the previous literature and the relevant theories and concepts that tackle rebel governance. Using these theories, a number of hypotheses were deduced to test them on the two selected case studies; Hezbollah and the Democratic Union Party (PYD). The study compared between Hezbollah that is considered as a rebel group that survived the civil war and became part of the Lebanese government, and the PYD that is still struggling over dominance in Syria, and it is unclear whether it will be part of the post-war order or not. The study concluded that a rebel group that seeks to sustain its governance needs to consolidate its legitimacy among the population under its jurisdiction especially through providing goods, service and security in a consistent way.